KEPATUHAN WAJIB PAJAK ORANG PRIBADI BUKAN PEGAWAI: HUBUNGANNYA DENGAN PENDAPATAN DAN PERSEPSI WAJIB PAJAK - Ni Wayan Nuratni; Agus Wahyudi Salasa Gama; Anak Agung Made Sastrawan Putra (Universitas Triatma Mulya, 2023)
Taxpayer compliance is actually closely related to the perception of taxpayers in assessing the tax itself. In the last five years, the taxpayer compliance ratio has never reached the target set. The purpose of this study was to determine the effect of income variables and taxpayer perceptions on individual non-employee taxpayer compliance. This study uses a quantitative approach with a research instrument in the form of a questionnaire. The sample used is 137 individual non-employee taxpayers at KPP Pratama North Badung. This study uses six independent variables, namely income, taxpayers' perceptions of tax sanctions, taxpayers' perceptions of law enforcement, taxpayers' perceptions of fair tax treatment, taxpayers' perceptions of transparent and accountable use of tax money, and taxpayers' perceptions of tax incentives. Data analysis was carried out using the structural equation model (SEM) method, with the AMOS 22 program. The results of the analysis show that individual non-employee taxpayer compliance behavior is influenced by income factors and taxpayer perceptions. All independent variables have a positive effect on taxpayer compliance.